2007
DOI: 10.1016/j.cub.2007.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Vocal-Tract Resonances as Indexical Cues in Rhesus Monkeys

Abstract: SummaryVocal-tract resonances (or formants) are acoustic signatures in the voice and are related to the shape and length of the vocal tract. Formants play an important role in human communication, helping us not only to distinguish several different speech sounds [1], but also to extract important information related to the physical characteristics of the speaker, so-called indexical cues. How did formants come to play such an important role in human vocal communication? One hypothesis suggests that the ancest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 43 publications
5
127
0
Order By: Relevance
“…Rhesus monkeys use formants in species-specific vocalizations as indexical cues as well (Ghazanfar et al 2007) and although not many studies have investigated similar phenomena in bird vocalizations it has been shown that whooping cranes, for example, can perceive changes in formant frequencies in their own species calls and exhibit a different response pattern to calls with higher formants compared with lower formants (Fitch & Kelley 2000). These results led to the speculation that formant perception originally emerged in a wide range of species to assess information about the physical characteristics of conspecifics, and that human speech has exploited the already existing sensitivity for formant perception (Fitch 2000;Ghazanfar et al 2007). It can, of course, not be ruled out completely that unique perceptual abilities to facilitate speech perception did evolve in humans, or that the observed abilities evolved separately in birds and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Rhesus monkeys use formants in species-specific vocalizations as indexical cues as well (Ghazanfar et al 2007) and although not many studies have investigated similar phenomena in bird vocalizations it has been shown that whooping cranes, for example, can perceive changes in formant frequencies in their own species calls and exhibit a different response pattern to calls with higher formants compared with lower formants (Fitch & Kelley 2000). These results led to the speculation that formant perception originally emerged in a wide range of species to assess information about the physical characteristics of conspecifics, and that human speech has exploited the already existing sensitivity for formant perception (Fitch 2000;Ghazanfar et al 2007). It can, of course, not be ruled out completely that unique perceptual abilities to facilitate speech perception did evolve in humans, or that the observed abilities evolved separately in birds and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Identity information is present in both the face and the voice and recently there has been considerable interest in the ability of both humans and animals to use this information (e.g., Ghazanfar et al, 2007). Individuals can estimate body size, age and gender from both faces and voices.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…This would provide an account for the considerable fixations made to the eyes during audiovisual speech experiments (e.g. Vatikiotis-Bateson, Eigsti, Yano & Munhall, 1998;Paré, Richler, ten Hove & Munhall, 2003;Lansing & McConkie, 2003) even though the eyes are not a particularly informative facial feature for perceiving speech sounds.Identity information is present in both the face and the voice and recently there has been considerable interest in the ability of both humans and animals to use this information (e.g., Ghazanfar et al, 2007). Individuals can estimate body size, age and gender from both faces and voices.…”
mentioning
confidence: 99%
“…Formants also correlate with vocal tract length in mammals (Canis familiaris: Riede and Fitch 1999;Cervus elaphus: Reby and McComb 2003) and may represent an indexical cue (Ghazanfar et al 2007) for receivers, thus providing information related to the physical characteristics of the emitter.…”
Section: Introductionmentioning
confidence: 99%